The Assessment of Building Energy Performance: Thammasat University, Rangsit Campus - Srisutapan, Awiroot (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This research aims to assess buildings in terms of energy performance and propose the appropriate guidelines to renovate buildings in Thammasat University, Rangsit Campus. By investigating, collecting, and analyzing data of the selected buildings in present condition in various aspects, the results indicated that the overall energy performances of buildings were lower than minimum criteria. Principal causes of failure can be concluded as follows 1) some buildings were designed before the Energy Conservation Promotion Act B.E. 2535 was announced, so the architects had no guidelines to follow 2) because the policy of energy conservation of buildings in campus had not been clearly defined, the energy performance of the new buildings were not considered 3) the cooling technique was changed from natural ventilation to air conditioning, but the building components were not improved 4) no energy conservation-expert team participated in design and development processes and 5) in terms of management, neglectful behaviors directly affected on energy consumption. For better performance, thermal heat gain must be decreased by 1) adding insulation to walls and roofs 2) providing effective shading devices 3) shading the buildings and surrounding with vegetations and 4) air conditioning using must be managed.